Monitoring the Land Covers Around Al- Razaza Lake/ Iraq Based Upon Multi-Temporal Analysis Technique - Sabah Noori Kadhum; Esraa Salam Alsudani (Al-Mustansiriyah Journal of Science, 2021)
Remote sensing techniques are very important for the identification of land cover patterns and monitoring changes that occurred, thus three different periods were taken for the Al-Razaza lake region.  The Summer and spring months were chosen because climate changes were observed and their effect on land covers was monitored.  According to the applied supervised classification, the study area was divided into four land covers, nearly closed Al – Razaza Lake was deeper in its western portions, thick vegetation cover was found. The eastern and southern portion of the lake was bounded by desertic and semi-desertic land. The water level in the lake was fluctuating with different seasons. During the period 2000 and 2015 the area of the lake was height decreased around 320 Km2.   Climate changes led to increasing drying out water areas and a high increase in the number of saline areas in 2015. This study shows a significant decrease in water cover In terms of depth and area of the lake due to the large decline in the value of the NDWI index.